1977
DOI: 10.1017/s0021859600037424
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a wide range of fertilizer nitrogen application rates and defoliation intervals on the dry-matter production, seasonal response to nitrogen, persistence and aspects of chemical composition of perennial ryegrass (Lolium perennecv. S.24)

Abstract: A small-plot experiment was made to assess the influence on dry-matter output from grass of a wide range of fertilizer nitrogen and defoliation interval treatments. There were five defoliation treatments, 22, 28, 45, 75 and 112-day regrowth intervals throughout the growing season each at six levels of nitrogen application, ranging by 300 kg increments from 0 to 1500 kg/ha/year.There was a marked interaction effect between treatments; a positive dry-matter response was maintained to a higher level of applied ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
2

Year Published

1981
1981
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 24 publications
4
19
2
Order By: Relevance
“…Cutting experiments have shown that a significant proportion of the difference between long and short defoliation intervals may arise from differences in yield at first defoliation (Bartholomew & Chestnutt, 1977). The difference in defoliation interval in the present experiment was nominally 15 days but, since grazing on both interval treatments started on the same day, mean difference in time of initial defoliation over the first cycle of each rotation length treatment was only 6 days.…”
Section: Net Herbage Accumulationcontrasting
confidence: 50%
See 1 more Smart Citation
“…Cutting experiments have shown that a significant proportion of the difference between long and short defoliation intervals may arise from differences in yield at first defoliation (Bartholomew & Chestnutt, 1977). The difference in defoliation interval in the present experiment was nominally 15 days but, since grazing on both interval treatments started on the same day, mean difference in time of initial defoliation over the first cycle of each rotation length treatment was only 6 days.…”
Section: Net Herbage Accumulationcontrasting
confidence: 50%
“…The extent to which these manipulations may have affected production is difficult to assess although, since variation in herbage allowance throughout the experiment had little influence on NHA, the effect of grazing pressure manipulation on grass yield is likely to be small. It is estimated that under a cutting regime the difference in initial defoliation date would reduce the difference in total yield over the season at the two defoliation intervals from 30 to 24% (Bartholomew & Chestnutt, 1977;Binnie, Chestnutt & Murdoch (1980). It was perhaps rather surprising to find that herbage allowance treatments produced no significant effect on NHA, since increasing degree of defoliation is considered to reduce D.M.…”
Section: Net Herbage Accumulationmentioning
confidence: 99%
“…Maximum DM production in a study on perennial ryegrass was obtained with a 10.5-week cutting interval (Bartholomew & Chestnutt 1977), which was only 11% more than the production obtained with a 6.5-week interval. In another study, Wilman (1975) obtained maximum DM production with Italian ryegrass after an 11 »week regrowth period.…”
Section: >mentioning
confidence: 74%
“…Increased N fertilisation results in an increase in dry matter (DM) production, but this increase levels off above a certain critical N application level. For ryegrass this critical level is reached with approximately 400 to 500 kg N ha 4 a" 1 (Cowling & Lockyer 1970;Bartholomew & Chestnutt 1977;Smith 1977;Pimentai et at. 1978;Hart & Widdowson 1981;Ehlig & Hagemann 1982;Eckard 1989).…”
Section: Introductionmentioning
confidence: 99%
“…In other environments, yield of these pastures has been related to total N applied, rather than to an application rate per defoliation. The recommended rate is generally about 300-500 kg N/ha.year (Bartholomew and Chestnutt 1977;Morrison 1980;Eckard 1989); this is equivalent to the local recommendations of 5-8 applications at 60 kg N/ha.application.…”
mentioning
confidence: 98%